A Case Study of Interactive Tabletops in Education: Attitudes, Issues of Orientation and Asymmetric Collaboration - Christofi, Maria; Ioannou, Andri; Vasiliou, Christina (My University, 2013)
This paper is concerned with the exploration of an educational tabletop application designed to facilitate collaboration amongst young learners while they learn about the “Plants of Cyprus”. The application was used by 28 third-graders during a scheduled visit at the Cyprus Center of Environmental Research and Education. We report empirical findings concerning the participants’ interactions around the table as well as their attitudes regarding the activity. Findings demonstrated that the students collaborated intensively in completing the task and they were overwhelmingly positive about the experience. The paper discusses issues of orientation of the on-display learning artifacts, which encouraged learners to move at a new location around the table to “correct” the orientation. Also, the study raises concerns regarding asymmetrical forms of collaboration, where peers dominated the activity despite the equal access on the tabletop surface.
Keywords: Interactive Tabletops; Collaborative Learning; Interactions; Attitudes; Orientation; Asymmetric Collaboration